Ouabain Suppresses IL-6/STAT3 Signaling and Promotes Cytokine Secretion in Cultured Skeletal Muscle Cells - Pirkmajer, Sergej; Bezjak, Katja; Matkovič, Urška; Dolinar, Klemen; Jiang, Lake Q.; Miš, Katarina; Gros, Katarina; Milovanova, Kseniya; Pirkmajer, Katja Perdan; Marš, Tomaž; Kapilevich, Leonid; Chibalin, Alexander V. (Frontiers in Physiology, 2020)
The cardiotonic steroids (CTS), such as ouabain and marinobufagenin, are thought to be adrenocortical hormones secreted during exercise and the stress response. The catalytic α-subunit of Na,K-ATPase (NKA) is a CTS receptor, whose largest pool is located in skeletal muscles, indicating that muscles are a major target for CTS. Skeletal muscles contribute to adaptations to exercise by secreting interleukin-6 (IL-6) and plethora of other cytokines, which exert paracrine and endocrine effects in muscles and non-muscle tissues. Here we determined whether ouabain, a prototypical CTS, modulates IL-6 signaling and secretion in the cultured human skeletal muscle cells. Ouabain (2.5-50 nM) suppressed the abundance of STAT3, a key transcription factor downstream of the IL-6 receptor, as well as its basal and IL-6-stimulated phosphorylation. Conversely, ouabain (50 nM) increased the phosphorylation of ERK1/2, Akt, p70S6K, and S6 ribosomal protein, indicating activation of the ERK1/2 and the Akt-mTOR pathways. Proteasome inhibitor MG-132 blocked the ouabain-induced suppression of the total STAT3, but did not prevent the dephosphorylation of STAT3. Ouabain (50 nM) suppressed hypoxia-inducible factor-1α (HIF-1α), a modulator of STAT3 signaling, but gene silencing of HIF-1α and/or its partner protein HIF-1β did not mimic effects of ouabain on the phosphorylation of STAT3. Ouabain (50 nM) failed to suppress the phosphorylation of STAT3 and HIF-1α in rat L6 skeletal muscle cells, which express the ouabain-resistant α1-subunit of NKA. We also found that ouabain (100 nM) promoted the secretion of IL-6, IL-8, GM-CSF, and TNF-α from the skeletal muscle cells of healthy subjects, and the secretion of GM-CSF from cells of subjects with the type 2 diabetes. Marinobufagenin (10 nM), another important CTS, did not alter the secretion of these cytokines. In conclusion, our study shows that ouabain suppresses the IL-6 signaling via STAT3, but promotes the secretion of IL-6 and other cytokines, which might represent a negative feedback in the IL-6/STAT3 pathway. Collectively, our results implicate a role for CTS and NKA in regulation of the IL-6 signaling and secretion in skeletal muscle.